Identification of a fat-soluble fraction of Sparganium stoloniferum that inhibits cervical cancer HeLa cells - Zhang,Junwu (2016)
ABSTRACT Context The rizoma of Sparganium stoloniferum has been used as a traditional Chinese medicinal herb for thousands of years. Sparganium stoloniferum is a stasis-breaking drug to treat a wide range of diseases including cancer,however, its activity of extract on cervical cancer HeLa cells and the mechanisms remains unknown. Objective This study aimed to screen Sparganium stoloniferum extract for its inhibitory effects on cervical cancer HeLa cells. Materials and methods Sparganium stoloniferum was extracted with 95% ethanol under reflux, and the extracts were preliminary separated by silica gel column chromatography. MTT assay and flow cytometry were used to determine the inhibitory effects of three fractions on HeLa cells. In addition, GC-MS was performed to analyze the chemical composition of the active fraction. Results Sample II showed a dose-dependent inhibition of HeLa cell growth, with an inhibition rate of more than 30%, whereas the inhibition rates of Samples I and III were less than 30%. Interestingly, Samples I and III had no effect on apoptosis, in contrast to Sample II, which significantly promoted HeLa cell apoptosis, in a dose-dependent manner. GC-MS was performed to analyze the chemical components of Sample II: steroids were found to be the major components with a relative content of 73.905%, while six known compounds were obtained for the first time. Discussion and conclusion This study provided a novel insight for further research of active fractions of Sparganium stoloniferum, in accordance with the basic principle and theory of traditional Chinese medicine (TCM), and will promote the shift of effective substance study, from monomeric chemical compounds to active fractions.